The Relationship of Food Leftovers and Students' Level of Satisfaction with the Food Served with the Nutritional Status of Nurul Ulum Islamic Boarding Students in Peureulak, East Aceh - Rizki Sofiani; Arnisam Arnisam (International Journal Labs, 2022)
Nutritional status is a condition determined by the degree of food whose physical impact can be measured. Adolescents are a group that is vulnerable to experiencing nutritional problems. The prevalence of wasting among adolescents aged 16-18 years nationally is 9.4% (1.9% are very thin and 7.5% are thin). The prevalence of adolescent nutritional status in Aceh among adolescents aged 16–18 years is 7.3% thin, 12.6% fat, and 4.6% obese. Good nutritional status must be balanced with incoming and outgoing energy and protein intake. One way to measure a person's food intake is by weighing food waste. This research is descriptive and analytical in nature, using a cross-sectional approach with a total sampling of 60 people carried out in February 2019 at the Nurul Ulum Islamic Boarding School, Peureulak, East Aceh. The research variables are food waste with nutritional status and level of satisfaction with nutritional status. Descriptive data analysis included frequency distribution and percentages with the Chi-square test. The results of this study showed that 42 people (70.0%) had a normal BMI, 10 people were thin (16.7%), and 8 people were obese (13.3%). The results of female students' food waste show an average of 20.1%. Most of the female students at the Nurul Ulum Islamic Boarding School in Pereulak, East Aceh, had a lot of food leftovers, 35 people (58.3%) and 25 people (41.7%) a little food waste, and for this category, the level of satisfaction showed that the average was 68.9 The majority of those who were dissatisfied were 45 people (75%), and those who were satisfied were 15 people (25%). The results of this research concluded that there was a relationship between food waste and the nutritional status of female students at the Nurul Ulum Islamic Boarding School, Pereulak, East Aceh, marked with a P value of 0.023 or (P<0.05), while the relationship between female student satisfaction and the nutritional status of female students at the Nurul Ulum Islamic Boarding School, Pereulak Aceh East there is no relationship indicated by a P value of 0.921 or (P>0.05).